ANALISIS KEPUASAN KERJA KARYAWAN KOPERASI SIMPAN PINJAM MITRA USAHA - Badaruddin Badaruddin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The purpose of this study was to determine the level of employee satisfaction Credit Unions Partner Usaha.Pengukuran done by taking the respondents across employees at Credit Unions Business Partners that is 76 people. From the results and discussion obtained the following conclusions: (1) Based on the position of respondents currently Satisfaction Survey Employees Credit Unions Business Partners, the managerial position has the satisfaction index of highs and lows on the position of Marketing and (2) Dimensions must receive attention Credit Unions Partner Enterprises according to employees based on position include career development, training, innovation, management, quality, working conditions, safety, communication and supervision.